Mengatasi Penyimpangan Asumsi Normalitas pada Pemodelan Persamaan Struktural Menggunakan Bootstrap - Otok, Bambang Widjanarko; Guritno, Suryo; Subanar, .; Haryatmi, Sri (Jurnal Widya Manajemen & Akuntansi, 2007)
All important assumption which must fulfill in Structural Equation Modelling (SEM) is data of continue and distribution multivariate normal. If do not fulfill will affect at result of analysis, that is failure in conducting convergence or yield the solving of inappropriate. One of the way of to overcome the mentioned is bootstrap method. So that this is research more focused in overcoming deviation of assumption of normality at SEM model with bootstrop method at case influence of commitment to performance through behavior. Or equally look for appropriate solution at data which below par with bootstrap method at case. Result of research, indicating that parameter coefficient of bootstrap can overcome deviation of assumption normality, yielding solution matching with data. Professional commitment have an effect on to behavioral and organizational commitment of activity. Wile organizational commitment have an effect on to behavior work and activity performance, behavioral and organizational commitment of activity represent variable having an effect on indirectly at professional commitment in influencing performance.